I will speak up if I feel energetic: Effects of supervisor humor on employee voice - Li, Daiheng; Liu, Pan; Li, Shuang; He, Jieya (Frontiers in Psychology, 2023)
Extant literature on supervisor humor predominantly documents its beneficial effects on the organization, but its dark side receives little attention. Drawing on ego depletion theory, we proposed a conceptual model to examine the effects of two interpersonal types of supervisor humor (i.e., affiliative humor and aggressive humor) on employee voice. An empirical study with a sample covering 257 employees in China indicated that supervisor aggressive humor was negatively related to voice behaviors via depleting employees’ resource. In contrast, supervisor affiliative humor was positively related to voice behaviors owing to less depletion of employees. Contrary to prediction, emotional intelligence enhanced the positive effect of supervisor aggressive humor on employees’ depletion. Important theoretical and practical implications were discussed.